Comunicação em ouvidoria: um caso de prática organizacional - NOBRE NETO, Pedro Germano (2021)
This dissertation is the result of a research motivated by the need to understand the communicative practices established by the Ebserh Ombudsman Network, from the perspective of the Ombudsman manifestation triad, satisfaction survey and access to information, in the perspective that they can be analyzed in the context of organizational communication. Thus, there was a need for perception of the relationship between Ombudsman and Communication by a group of 39 ombudsmen, characterized by an understanding of the social network as the construction of relational bonds between individuals and making use of a qualitative methodology that made use of a research bibliographic about the worked categories; documentary research on current legislation and regulations; participant observation as the researcher is an actor in the process; questionnaire, in order to draw information from the combudsmen; and interview, with a view to deepening the professionals' opinions. It was concluded that the Ombudsman should take into account the uniqueness and circumstances of users, as well as strengthen the links between the public service and the citizen. In addition to the dissertation text, a Communication Model in the Ombudsman's Office was produced, with two actions, namely: a training proposal and a guide with general guidelines for communicative practices in the Ombudsman's Office.